HUBUNGAN TINGKAT PENGETAHUAN TENTANG PENYAKIT DEMAM BERDARAH DENGUE DENGAN TINDAKAN PEMBERANTASAN SARANG NYAMUK - Kristanto, Budi; Setyaningsih, Rahayu (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. According to Indonesian Ministry of Health in February 2019, there were 16,692 cases DHF with 169 deaths, this has increased compared to 2018 which only 13,683 cases with 133 died. Central Java is one of the provinces with the most cases and including Kenokorejo Village Sukoharjo Regency where almost every year there are dengue cases.The Aim of the Study. To Know the relationship between the level of knowledge about Dengue Hemorrhagic Fever and the eradication of mosquito nests.Subject and Method. Observational analytic research, correlation design with cross sectional approach. Respondents were 47 Residents of the Village of Kenokorejo taken by sampling saturation. Data were analyzed using Pearson Correlation.Result. The majority of respondents have good category knowledge of 95.74%, while less than 4.25%, the majority of respondents with good PSN actions are 53.19%, and categories of less 6.38%.Conclusion. There is no relationship between the level of DHF knowledge with mosquito eradication (p = 0.367).Keywords: dengue hemorrhagic fever, eradication of mosquito nests, knowledgeKorespondensi: Budi Kristanto. AKPER PANTI KOSALA SURAKARTA. Jalan Raya Solo-Baki Km. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: budikrist18@gmail.com.